2013
DOI: 10.1002/hep.26122
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced intraoperative ultrasonography for vascular imaging of hepatocellular carcinoma: Clinical and biological significance

Abstract: Abnormal tumor vascularity is one of the typical features of hepatocellular carcinoma (HCC). In this study, the significance of contrast-enhanced intraoperative ultrasonography (CEIOUS) images of HCC vasculature was evaluated by clinicopathological and gene expression analyses. We enrolled 82 patients who underwent curative hepatic resection for HCC with CEIOUS. Clinicopathological and gene expression analyses were performed according to CEIOUS vasculature patterns. CEIOUS images of HCC vasculatures were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…A recent meta‐analysis confirmed that a wide surgical margin (≥1 cm) can increase long‐term OS and DFS and improve prognosis in patients with HCC compared with a narrow surgical margin (<1 cm) . Locating the tumor by intraoperative laparoscopic ultrasonography and careful dissection through the laparoscopic lens make it possible to keep the intended margin . Risk of tumor seeding was another fear regarding laparoscopic resection of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis confirmed that a wide surgical margin (≥1 cm) can increase long‐term OS and DFS and improve prognosis in patients with HCC compared with a narrow surgical margin (<1 cm) . Locating the tumor by intraoperative laparoscopic ultrasonography and careful dissection through the laparoscopic lens make it possible to keep the intended margin . Risk of tumor seeding was another fear regarding laparoscopic resection of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al (23) reported that the MFI pattern classification may aid the evaluation of the differentiation grade of HCC. In addition, Sato et al (24) reported that the MFI pattern classification may be an individual predictive factor of a poor prognosis in patients with HCC. These studies suggest that the MFI findings of the intratumoral vascular architecture may aid the evaluation of the differentiation grade of HCC.…”
Section: A B Discussionmentioning
confidence: 99%
“…Perflubutane, the contrast medium used for CEUS comprises microbubbles that do not seep into the stroma, and it can therefore display detailed images of tumor vessels and blood flow (18,19). Thus, it is a standard test to distinguish hepatomas containing tumor vessels (20) in the liver, and a factor for predicting the prognosis of hepatocellular carcinoma (32). Although CEUS has been considered useful for detecting malignant breast cancer, only a few studies (26,27) of small patient cohorts have assessed its ability to predict pCR after NAC and thus supporting evidence is insufficient.…”
Section: Discussionmentioning
confidence: 99%